(untitled) (Avocetta, 2024)
Mixed clutches are relatively uncommon among colonial shorebirds and challenging to document. Here, we report the co-occurrence of three species’ eggs, belonging to Pied Avocet Recurvirostra avosetta, Little Tern Sternula albifrons and Common Tern Sterna hirundo, in the same nest within a large colony in the Marano and Grado Lagoon, Friuli Venezia Giulia. To our knowledge, it is the first record with more than two species among Charadriiformes. We discuss the possible explanation concerning the limited suitable nesting space in a human-made breeding habitat. These findings are rarely reported despite their importance for comprehending the phenomenon from an ecological perspective.